How Do Innovative Schools Create the Conditions for Reflective Practice? - Birch, Daniel (Auckland University of Technology, 2022)
A significant focus of innovative schooling is the requirement for teaching staff to engage in reflective practice to deeply investigate their impact on student outcomes and how they work effectively with their colleagues and collaborators. There is research evidence that reflection is an important part of the journey for educators. From Dewey in 1910 to more contemporaries such as Argyris and Schön in the late 1990s, models and frameworks have been published for subjects to engage with. The Teaching Council of Aotearoa (2020) has also engaged in the need for reflective practice through its creation of the ‘professional growth cycle’, a shift from a more formalised appraisal process. The Teaching Council has, however, produced a simplistic framework for school leaders to implement allowing for staff to demonstrate some levels of competence within their practice. My goal with this study was to establish a more robust process that synthesised the work of the Teaching Council, so compliance occurs, with the work of researchers and critical friends. The resulting artefact I developed provides a levelled process in its approach to allow multiple entry points. The levels are designed to develop complexity of cognitive engagement as staff work through them. Leaders must engage in the process and develop a high trust culture to allow staff to travel through the artefact at a pace that represents their experience and skills in critical reflection. The artefact supports the processes needed for successful critical reflection, educators can grow in their ability to be more effective and leaders will have a framework to link to the professional growth cycle (Teaching Council of Aotearoa, 2020) and maintain a level of compliance. While the growth cycle is new (Teaching Council of Aotearoa, 2020), reflection, through Teaching as Inquiry, has been part of the New Zealand Curriculum since 2007. The missing aspects of both the new professional growth cycle and the existing Teaching as Inquiry model, is the link to the educative purpose of the school, connecting the reflective practice to the vision, values and pedagogy, so reflection is targeted. My artefact brings that dimension to the fore. The autoethnographical approach to this exegesis brings together my experiences as an experienced educator and the processes required to develop an artefact. This practice-based approach has, at its centre, an artefact that combines the work of researchers, practitioners and critical friends. The artefact is attached to this exegesis as a separate document, and this exegesis sits alongside the artefact. This exegesis collates relevant research from those educators and academics who have studied and used reflective practice for long periods of time as well as learnings from those who have been working in innovative spaces for many years, developing critical reflection through a high trust relational model. While the focus in this study has been on innovative environments, critical reflection should be a crucial aspect of all schools. The need we see for staff to make sense of their own practice is intertwined with the nature of how their school empowers educators to grow.